2022
DOI: 10.1016/j.jadohealth.2021.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Protective Factors Associated With Mental Health Outcomes in Sexual Minority Youth

Abstract: The aim of this study is to identify and evaluate the efficacy of adolescent protective factors against mental health (MH) outcomes in young adulthood of sexual minority identifying youth (SMY). Methods: Using data from the National Longitudinal Study of Adolescent to Adult Health, we identified potential protective factors (e.g., individual factors like self-esteem, family factors like family communication, and community factors like caring teachers) at baseline (1994) when the sample was school-aged for SMY.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…In line with previous reviews, our study confirms the association of individual, relationship, community and societal factors with the mental health of CYP [13][14][15][16][17][18][19][20][21]29]. Unlike previous reviews there were mixed finding for some of the key factors like parent-to-parent relationship and social status.…”
Section: Comparison To Previous Reviewssupporting
confidence: 89%
See 1 more Smart Citation
“…In line with previous reviews, our study confirms the association of individual, relationship, community and societal factors with the mental health of CYP [13][14][15][16][17][18][19][20][21]29]. Unlike previous reviews there were mixed finding for some of the key factors like parent-to-parent relationship and social status.…”
Section: Comparison To Previous Reviewssupporting
confidence: 89%
“…As for marginalised groups, based on ethnicity or sexuality, experiences of discrimination were also identified as having a negative association with mental health [9,20]. Conversely, improved self-esteem and optimism have been associated with positive mental health and resilient outcomes [13,21]. While acknowledging the efforts of researchers in the previous reviews, the evidence from some regions like the English-speaking Caribbean is still under-represented.…”
Section: Introductionmentioning
confidence: 95%
“…However, studies in recent years have identified a range of both risk and protective contextual factors (e.g., individual, family/peer, and community/neighborhood) associated with AOD use and well-being among SGM adolescents and emerging adults. For example, factors such as self-esteem, peer and family support, and supportive school/campus environments have been linked to better health and well-being among SGM adolescents and emerging adults (Hatzenbuehler & Keyes, 2013; Parmar et al, 2022; Shattuck et al, 2022). In contrast, factors such as family rejection (Ryan et al, 2009), bullying/victimization, exposure to “conversion therapy,” health/service provider discrimination, and community/neighborhood factors have been correlated with poorer outcomes (Forsythe et al, 2022; Hatzenbuehler, 2010; Williams & Chapman, 2011; Woodford & Kulick, 2015).…”
Section: Gaps In Understanding Of Contextual Factors and Lived Experi...mentioning
confidence: 99%
“…Generation 2 (Gen2) self-report of race/ethnicity has not been ascertained. There were 2868 live births (Gen2), followed up at the ages of 1, 2, 3,5,8,10,14,17,20,22, and 27 years. Follow-up of Gen1 and Gen2 participants is ongoing.…”
Section: Design and Participantsmentioning
confidence: 99%